The Influence of Gender and Menopausal Status on Hba1c Variation in a Big Data Study of a Saudi Population - Alghamdi, Abdullah S.; Alqadi, Abdulaziz; Jenkins, Richard O.; Haris, Parvez I. (Current Diabetes Reviews, 2021)
Background: Glycated haemoglobin (HbA1c) is the gold standard measurement in the screening, diagnosis and monitoring of diabetes mellitus. Saudi Arabia has a high prevalence of diabetes mellitus that is expected to rise, and the HbA1c test is commonly used in the screening, diagnosis and monitoring of diabetes. Objective: This study aims to assess the impact of age and gender on HbA1c levels, and the influence of menopausal status on HbA1c variation in a large group of Saudis. Methods: Age, gender, and HbA1c results of 168,614 Saudi adult individuals were obtained from their medical records. Patients’ records were extracted irrespective of their status regarding the presence of diabetes and the status of glycaemic control. Linear regression models were used for predicting HbA1c from age and gender, and their interaction term. HbA1c levels were compared between genders in different age groups and different HbA1c categories. Results: There was a statistically significant positive correlation between age and HbA1c levels, where for each ten years increase in age, HbA1c increased by 0.35%. Although the overall mean HbA1c in women was significantly lower than in men (P < 0.001), women showed a significant increase in HbA1c with older age compared to men (B = 0.014, P < 0.001). Furthermore, the mean HbA1c levels in the age group > 50 years was significantly higher than before that age (P < 0.001). Thus, HbA1c increased by 1.118% in age > 50 years group compared to age ≤ 50 years, and this increase in HbA1c was significantly higher in women compared to men (B = 0.495, P < 0.001). Conclusion: HbA1c levels are lower in women before the estimated menopausal age, which should be taken into consideration when using HbA1c for screening, diagnosis, and monitoring of diabetes in Saudi adult women. The short lifespan of red blood cells, due to loss of blood through menstruation, in women before menopause age, is a possible reason for these variations.
Keywords: menopause